Is it possible the bond between university, popular education and territory? Reflections and learnings from the “Encuentro de Redes” experiencie in Córdoba - Arévalo, Luis Alberto; Ambroggio, Joaquín; Pez, Tamara; Bado, Marcelo Daniel (Universidad Nacional de Villa María, 2021)
The present work recovers some reflections and learnings wich araise from the “Encuentro de Redes” experiencie that took place in the city of Córdoba, conceptualized as an exchanging place between referents of networks and members of the Universidad Nacional Villa María. The axis of this paper is focused in educations-learning proces that araise from the bond between territories and the university, tending to the production of situated knowledge and collectively built from dialogues of knowledges between practice and theory.             In order of that, we look, from challenges and results that we have picked up from the “Encuentros de Redes” experiencie, to describe some common traits of the nets, their difficulties and challenges of the territory in wich they act, and some interrogants that presents to us in the actual context, that requieres the common search of answers between territorie actors and members of the university, with the aim of discus the classic distinction between practice and theory and character endogamic and elitis of the academic field, that legitimies a kind of knowledge that is far away from the social proces, that is eclusively reproduced in a close ambit of especialists and academics.